Akulturasi Budaya Islam, Jawa dan Tionghoa di Pesarean Gunung Kawi Kabupaten Malang - Dita Karisma Fahriani; Bagus Wahyu Setyawan (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
Cultural acculturation is a combination of cultural elements by a person or even a group of people against other cultures as a result of the interaction between these cultures by not leaving the original cultural elements. This cultural acculturation can occur in traditional ceremonies, traditions, and building architecture. This study examines the acculturation of Islamic, Javanese and Chinese cultures in Pesarean Gunung Kawi, Malang Regency. The purpose of this study is to (1) describe the nature of cultural acculturation, (2) describe the forms of acculturation of Islamic, Javanese and Chinese culture in Pesarean Gunung Kawi, Malang Regency. This study used descriptive qualitative method. Researchers used Youtube videos to get research data. The data collection technique used is the note-taking technique. The results of this study indicate that there is an acculturation of Islamic, Javanese, and Chinese cultures in Gunung Kawi, Malang Regency. This cultural acculturation can be well received by the community so as to create harmony.